Co-creating water knowledge: a community perspective - Castelli, G.; Howard, B. C.; Adyel, T. M.; AghaKouchak, A.; Agramont, A.; Aksoy, H.; Alba, R.; Alencar, P. H. L.; Amanambu, A. C.; Aslam, H.; Bharati, L.; Bos-Burgering, L.; et al. (Taylor and Francis, 2025)
Navigating the complexities of global and local water resources challenges requires collaboration and mutual learning among diverse knowledge systems and disciplines. However, Western philosophical approaches to generating knowledge have prevailed in water management and hydrology, often overlooking community priorities, practices and perspectives, and power asymmetries - including gender inequalities, racism, and colonial injustices. In this perspective paper, we explore the co-creation of water knowledge (CCWK) concept to value multiple and diverse forms of knowledge. We identify four overarching principles (inclusivity, openness, legitimacy, and actionability), highlighting the importance of establishing relationships and collaborative leadership, adopting key tools and techniques, and integrating knowledge for water resources management. Furthermore, we argue that prioritizing epistemic justice is essential for effective CCWK. To address these, we advocate for more interdisciplinary and reflexive research practices that challenge and disrupt Western scientific traditions shaped by functionalist and colonial legacies.